Indonesia’s Interests in the World Trade Organization and the Appellate Body Impasse: Questioning the Existence of Special and Differential Treatment - Setyo Utomo (Yuridika, 2023)
The World Trade Organization’s role in resolving international trade disputes is crucial, particularly in multilateral trade, which continues to grow alongside information disclosure and technology advancements. Dispute settlement systems often depend on the existence of the World Trade Organization’s Appellate Body. However, in 2019, the United States prevented new members from joining this body, resulting in dysfunction and instability. Moreover, in 2020, the term of the last sitting Appellate Body member expired. As members of the World Trade Organization, Indonesia and other developing nations receive preferential treatment, which frequently backfires when dealing with developed nations. The special and differential treatment provided to developing nations is supposed to minimize the distinctions between developed and developing nations. This study identified possible actions that Indonesia and other developing nations could take to put an end to the World Trade Organization’s impasse. To do this, they could use non-alignment diplomacy and waive their special and differential treatment. Both a conceptual approach and a literature review were used in this study.